Economic development program for person with disabilities: study at Majlis Persefahaman Pertubuhan Orang Kurang Upaya / Nur Hidayah Yusop - Yusop, Nur Hidayah (2018)
There is always improvement conducted by the government for the person with disabilities nowadays in the social and economy, such as giving place for them to sharpen their skills and also by organizing the economic development program for this group to participate with society. The purpose of this study is to identify economic development program conducted by MPPOK for the person with disabilities: Majlis Persefahaman Pertubuhan Orang Kurang Upaya Kelantan (MPPOK). This study focuses on three objectives which including; 1) type of economic development program that participated by participants of MPPOK, 2) impact of the economic development program in Majlis Persefahaman Pertubuhan OKU Kelantan (MPPOK) towards the person with disabilities and 3) problems and challenges faced by Majlis Persefahaman Pertubuhan OKU Kelantan (MPPOK) in improving the socio-economic for person with disabilities. This study is mixed method. A set of questionnaires were distributed to participants of MPPOK in Kota Bharu, Kelantan. The interview, conducted by the researcher to the highest committee to support the research objectives. The data collected through the questionnaires were analyzed using Statistical Product and Service Solutions (SPSS) software 20.0. In short, to sum up, this research was done to know the types of economic development program for persons with disabilities, the problem and challenges faced by people with disabilities and the impact of the program towards a person with disabilities.